The challenges and implementation in overcoming stunting by primary health care practitioners - Nurhannifah Rizky Tampubolon (Universitas Muhammadiyah Semarang, 2021)
Stunting events in Indonesia have fallen by around 7% in the last 5 years. That declined nationally has not been followed by a decrease in the prevalence of stunting in all primary health care (PHC), one of the PHC in Gunung Kidul Regency, has been able to reduce stunting prevalence in the last 3 years. The purpose of this study was to find out how the challenges and implementation faced by PHC practitioner Gunung Kidul Regency to overcoming the problem of stunting. Qualitative descriptive with single case study design. Data collection was conducted with semi-structured interviews with 5 PHC practitioners and triangulation of resources with cadres and village government. PHC practitioners village government and cadres had the same perspective to overcoming the problem of stunting, but the community was still unfamiliar. This was a challenge for health center practitioner. In addition, the measurement of growth of children under five carried out by cadres at the posyandu was considered to be inaccurate health workers. Therefore the implementation of the 1000 HPK Movement places more emphasis on strengthening the capacity of cadres in capturing stunting toddlers and how cadres provide infant and child feeding counseling so that stunting toddlers were more quickly detected and stunting problems were more likely to be overcome. PHC practitioners do the same perception with the village government and cadres in overcoming the problem of stunting, so that the collaboration has an impact on reducing the prevalence of stunting. The challenge faced by PHC practitioners is to maintain the accuracy of the measurement of infant growth by cadres in the posyandu by increasing assistance.